Anti-melanogenic effects of hydroxyethyl chrysin through the inhibition of tyrosinase activity: In vitro and in silico approaches - Yuna Lee; Ha-Yeon Song; Eui-Baek Byun (Heliyon)
The suppression of tyrosinase (TYR), a key enzyme in melanogenesis, has been suggested as an effective strategy for preventing melanin accumulation. We previously discovered the novel chrysin derivative hydroxyethyl chrysin (HE-chrysin) through an irradiation technique, which exerted higher anti-inflammatory and anti-cancer activities than original chrysin. In the present study, we explored whether HE-chrysin has antioxidant and anti-melanogenic capacity using in vitro B16F10 murine melanoma cells and in silico molecular docking. HE-chrysin exhibited enhanced antioxidant capacity in DPPH, ABTS, and FRAP assays, and it decreased cellular H2O2-stimulated reactive oxygen species levels in comparison to original chrysin. At 2.5 μM, HE-chrysin reduced 3-isobutyl-1-methylxanthine-stimulated melanin production significantly by suppressing intracellular TYR activity without cytotoxicity. Furthermore, molecular docking showed that HE-chrysin inhibited TYR activity by interacting with key residues (Glu256 and Asn260) and chelating Cu+ ions at the active site, with a binding free energy of −7.00 kcal/mol compared with arbutin (−5.12 kcal/mol). Our findings show that HE-chrysin is an anti-melanogenic candidate and a potential antioxidant for use in dermatologic therapy.